Legal Analysis of The Role of Diskominfo in Realizing Transparency & Public Participation in Gresik Regency - Zulvikar, Muhammad Vicki; Wardana, Dodi Jaya (Jurnal Daulat Hukum, 2025)
The government is responsible for maintaining the transparency of public services and improving public understanding of the law.  Data shows an increase in internet access in Indonesia between 2018 and 2022, with 98.44% of people using smartphones to access the internet in 2022.  Nevertheless, the APJII 2022-2023 survey shows that there are still many people who do not know the existing applications to improve public service transparency, especially in Gresik.  To combat the spread of hoaxes and help governments combat fake websites, decisive action is needed. This research shows that understanding the public is an important part of the democratic process, and increasing public awareness can help them better engage in public service. The findings of this study focus on the relationship between government and society is critical to achieving transparency, which is part of good governance. The findings of this study emphasize that electronic governance systems are very important to increase transparency and public participation. Improved training, technological infrastructure and application development are still needed, although there are still obstacles such as a lack of skilled human resources in the field of Information Technology. With the improvement of regulation and digital education, Diskominfo of Gresik Regency is expected to improve these conditions. To ensure public services run properly, applications such as Gresik Media must be used correctly. To ensure that the public can access clear and open policies and information, all government entities must support transparency in accordance with applicable law. All this is essential to support a good democracy.